Influence of Min-a-zel Plus on biochemical, microbiological and mycotoxicological parameters of lucerne silage - Đorđević Nenad 1; Adamović Milan; Grubić Goran; Koljajić Viliman; Bočarov-Stančić Aleksandra S. (Journal of Agricultural Sciences (Belgrade), 2003)
Lucerne of the 5th cut in the budding phase was ensiled in the experiment as fresh and wilted (DM= 220 and 360 g/kg), with two degrees of compression (520 and 380 g/dm3) and with added Min-a-zel plus as 2 g/kg green mass. The experiment was performed as the statistical model 2K. Min-a-zel plus used as 2 g/kg green mass had no influence on biochemical, microbiological and mycotoxicological parameters of lucerne silage. Compared to the beginning material, silages had more diverse microflora and more mycotoxins. All silages had high pH values and fermentation of the acetic acid type. Some improvement was achieved with wilting of the ensiling material. The least quality (V class) was obtained with fresh lucerne, which was less compressed, while others were ranked as IV quality class. The obtained results fortify the need for further investigations in developing correct doses of Min-a-zel plus to be used in ensiling of lucerne and other materials.